The Influence of Live Streaming and Materialism on Purchasing Decisions Fast Fashion Products Through Hedonic Motivation - Andrini, Raissa Fidela; Yuliati, Lilik Noor; Nurhayati, Popong (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: Live streaming is a feature where sellers promote shops and products directly to buyers which can influence consumer's materialistic nature and hedonic motivation and might impact on purchasing decisions. Purpose: The objectives of this research include identifying segments of Shopee live streaming users, analyzing the influence of live streaming and materialism on hedonic motivation variables and purchasing decisions for fast fashion products, and finding out how to manage live streaming to increase purchasing decisions for fast fashion products. Design/methodology/approach: The analytical method used was SEM-PLS and the data obtained was 213 samples by quantitative descriptive methods. Findings/Result: The research results show that the live streaming and materialism variables have a significant positive influence on the hedonic motivation variable and purchasing decisions for fast fashion products. This is because the materialism indicator is closely related to the hedonic motivation indicator, so it supports consumers in making purchasing decisions on live streaming platforms. The live streaming variable has a direct influence on the purchasing decision variable.Conclusion: The recommendation for MSMEs in the fashion sector, it is hoped that they can take advantage of the features available on Shopee in implementing product marketing through e-commerce.Originality/value (State of the art): This is the first time someone has used the SEM-PLS method to describe the relationship between factors and analyze factors on purchasing decisions. Keywords: fast fashion, hedonic motivation, live streaming, materialism, purchasing decision